Unveiling Baghdad's Urban Identity: A Comprehensive Study on the Dynamics of Urban Imprint - Asawer Abdulrahman Abbas; Shaimaa Hameed Hussein (Academia Open, 2024)
This research examines the "urban imprint" from an environmental and architectural perspective, focusing on Baghdad, Iraq. Analyzing Baghdad's urban evolution, considering social activities, ideological concepts, and economic factors, it aims to delineate characteristics contributing to the city's unique imprint. It underscores urban sprawl, population growth, and modernity's impact on the urban landscape, emphasizing the need for standards aligning with the city's identity. Findings reveal a dynamic process influenced by fixed and variable factors. Implications stress physical form assimilation to reflect local values, promoting sustainable urbanization. The study calls to halt Baghdad's urban deterioration, emphasizing the importance of regularly updating city-specific requirements for urban imprint. This research informs the global discourse on urban identity and design. Highlights: This research explores the concept of "urban imprint" with a focus on Baghdad, analyzing its historical evolution and factors shaping its unique urban identity. It highlights the ongoing dynamics of urban imprint influenced by urban sprawl, population growth, and modernization. The study emphasizes the need for tailored urban design standards to preserve local identity and promote sustainable urbanization. Keywords: Urban Imprint, Baghdad City, Urban Identity, Sustainable Urbanization, Environmental Factors